2019
DOI: 10.3390/nu11020427
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Nutrition Status and Antioxidant Capacity in Multiple Sclerosis Patients

Abstract: Background: Multiple sclerosis (MS) is a multifactorial disease with unknown etiology. It is assumed to result from interplay between genetic and environmental factors, including nutrition. We hypothesized that there are differences in nutritional parameters between MS patients and healthy controls. Methods: We examined 63 MS patients and 83 healthy controls. Nutritional status was determined by a dietary questionnaire, blood tests, quantification of cell membrane fatty acids, and serum antioxidant capacity. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 43 publications
(49 reference statements)
6
37
2
Order By: Relevance
“…Another reason for taking into consideration the iron supplementation is the fact that MS patients eat a more limited diet, with a lower average of 31 nutrients, including zinc, thiamin, and iron, when compared with healthy controls. In a study by Armon-Omer et al, 2019 blood tests showed that MS patients had significantly lower iron levels, with the lowest measures in the severe MS group [191]. In conclusion, it is possible that inadequate iron levels (both low and high) may be harmful in MS. Iron excess might increase free radicals, which may elevate oxidative stress, while iron reduction could decrease immune system function and cause an energy deficit due to loss of mitochondrial membrane potential [11].…”
Section: Iron and Multiple Sclerosismentioning
confidence: 91%
See 1 more Smart Citation
“…Another reason for taking into consideration the iron supplementation is the fact that MS patients eat a more limited diet, with a lower average of 31 nutrients, including zinc, thiamin, and iron, when compared with healthy controls. In a study by Armon-Omer et al, 2019 blood tests showed that MS patients had significantly lower iron levels, with the lowest measures in the severe MS group [191]. In conclusion, it is possible that inadequate iron levels (both low and high) may be harmful in MS. Iron excess might increase free radicals, which may elevate oxidative stress, while iron reduction could decrease immune system function and cause an energy deficit due to loss of mitochondrial membrane potential [11].…”
Section: Iron and Multiple Sclerosismentioning
confidence: 91%
“…In conclusion, it is possible that inadequate iron levels (both low and high) may be harmful in MS. Iron excess might increase free radicals, which may elevate oxidative stress, while iron reduction could decrease immune system function and cause an energy deficit due to loss of mitochondrial membrane potential [11]. In addition, Armon-Omer and coworkers found lower dietary copper intake in the MS group, which is an essential cofactor for many oxidative enzymes and is necessary for iron absorption and transfer [191].…”
Section: Iron and Multiple Sclerosismentioning
confidence: 99%
“…Iron deficiency is common in pregnancy. Iron deficiency can lead, among others, to decreased hemoglobin levels and reduced immunity [4,5,6,7,8]. In pregnancy, iron deficiency correlates with preterm delivery and low birthweight [4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Iron deficiency can lead, among others, to decreased hemoglobin levels and reduced immunity [4,5,6,7,8]. In pregnancy, iron deficiency correlates with preterm delivery and low birthweight [4,5,6,7,8]. In the other hand, high level of hemoglobin in women supplemented with iron was associated with an increase in the frequency of adverse effects, including hypertension disorders in pregnancy [4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…MS affects approximately 2.5 million people worldwide, with a tendency of prevalence data to considerably differ from one country to another, and registered highest percentages in North America (140 per 100.000) and Europe (108 per 100.000) (1)(2)(3). Although the etiopathogenesis is still unclear, genetic profiles predominantly involving immune response genes (HLA-DRB1, HLA-DPB1, HLA-A TNF genes), as well as inflammatory and environmental factors including Epstein-Barr virus infection, tobacco exposure, vitamin deficiencies and high saturated fat/carbohydrate diet are currently recognized among the most relevant causative agents (4)(5)(6)(7)(8)(9).…”
Section: U L T I P L E S C L E R O S I S ( M S ) I S a N A U T O I mentioning
confidence: 99%